Sustainable E-fuels: Green hydrogen, methanol and ammonia for carbon-neutral transportation - Reddy, Vennapusa Jagadeeswara; Hariram, N. P.; Maity, Rittick; Mohd Fairusham, Ghazali; Sudhakar, Kumarasamy (MDPI, 2023)
Increasingly stringent sustainability and decarbonization objectives drive investments in adopting environmentally friendly, low, and zero-carbon fuels. This study presents a comparative framework of green hydrogen, green ammonia, and green methanol production and application in a clear context. By harnessing publicly available data sources, including from the literature, this research delves into the evaluation of green fuels. Building on these insights, this study outlines the production process, application, and strategic pathways to transition into a greener economy by 2050. This envisioned transformation unfolds in three progressive steps: the utilization of green hydrogen, green ammonia, and green methanol as a sustainable fuel source for transport applications; the integration of these green fuels in industries; and the establishment of mechanisms for achieving the net zero. However, this research also reveals the formidable challenges of producing green hydrogen, green ammonia, and green methanol. These challenges encompass technological intricacies, economic barriers, societal considerations, and far-reaching policy implications necessitating collaborative efforts and innovative solutions to successfully develop and deploy green hydrogen, green ammonia, and green methanol. The findings unequivocally demonstrate that renewable energy sources play a pivotal role in enabling the production of these green fuels, positioning the global transition in the landscape of sustainable energy.